New complex dyes for wool - Edrah, Salem Mohamed (Univerzita Pardubice, 2008)
The set of mono azo dyes having in ortho position to tje azo group thiol, methylthio or methoxy group was prepared in the present work. The structure of these dyes was confirmed by MS and NMR spectra.
Keywords: acid dyes; mercapto-azo-dyes; metal complex dyes